Social Network Analysis of Integrated Medical Services for Hypertension – Using District Hospitals of Shanghai as a Model - Ziyou, Chen; Junshan, Li; Fen, Li; Yuanan, Lu (Journal of Hypertension and Cardiology, 2020)
Objective To examine the current linkage between different medical services for hypertension patients for enhanced integration among medical service systems. Methods A total of 18 hospitals and community medical centers from a district of Shanghai were enrolled for social network analysis which covered emergency visits and hospitalization records of 171,177 outpatients with hypertension. Stata software was used for data preprocessing and UCINET software was used for network analysis of medical service providers to quantify and visualize the network tightness and the "main role" of information delivery of the medical institution network in the area. Results The service network of hypertension consultation institutions in the region is closely connected as a whole, but the level of diagnosis and treatment of medical services in various communities varies widely, and the degree of association with higher-level medical institutions is not uniform. Conclusion Based on the limited tightness of various medical service providers, it is necessary to implement the responsibilities of individual medical institutions at different levels and pay more attention to improving the service capabilities of primary medical institutions for enhanced integrating medical services in future.
Keywords: Social network analysis; hypertension; integrated medical service; hospitals; community medical centers; Shanghai